Pengembangan Video Dongeng Animasi Panji Untuk Menstimulasi Perkembangan Moral Anak Usia 4 – 5 Tahun - Bella, Salsabella Aurellya Pratysta Putri; Ayu Titis Rukmana Sari; Epritha Kurnia Wati (Universitas Muhammadiyah Metro, 2025)
This research aims to develop innovative learning media in the form of Panji animated fairy tale videos to stimulate early childhood moral development. The background of this research shows the low morale of children, which can be seen from behaviors such as lack of patience, giving up easily, being disrespectful to teachers, and lack of empathy for friends. The learning approach used is still conventional, such as lecturing and writing, and has not utilized technology optimally. In addition, the lack of local culture-based media is an obstacle in instilling moral values while preserving cultural heritage. The method used is Research and Development (R&D) using the Borg and Gall development model. Data were collected through direct observation in the field, while data analysis used Aiken's Formula to assess the validity and feasibility of the media based on experts' assessment. The results of this study indicate that this local culture-based learning media has been achieved. This media is not only academically and technically feasible, but also succeeded in increasing children's involvement and moral understanding in accordance with the success indicators in the research objectives. The implication of this study is to contribute to early childhood learning theory, especially in the context of moral development, by showing that the use of local culture-based animated fairy tale video media (Panji story) is effective for stimulating children's moral development.